1984
DOI: 10.1084/jem.159.2.479
|View full text |Cite
|
Sign up to set email alerts
|

Activation specificity of arsonate-reactive T cell clones. Structural requirements for hapten recognition and comparison with monoclonal antibodies.

Abstract: We describe clones of hapten-specific inducer T cells from (BALB/c X A/J)F1 mice that respond to the p-azobenzenearsonate hapten conjugated to carrier proteins or directly conjugated to antigen-presenting cells. Some of the clones are also activated by haptens structurally related to arsonate. All activating analogues are recognized by each clone in association with the same major histocompatibility complex (MHC) protein as is arsonate. Weakly activating and nonactivating analogues are immunogenic in D2.GD amd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…2c illustrates measurements for individual GATA-3 alleles normalized to the nuclear radius, confirming the preferential association of GATA-3 with centromeric heterochromatin in polarized Th1 but not Th2 cells (p<0.01). This preferential association persisted in long term T cell lines and clones (p<0.01, Th1 clone D5 [23] versus Th2 clone D10 [24] and Th2 line GAD [25]). The cytogenetic position of the GATA-3 locus only 9.8 Mb from the centromere of chromosome 2 (Ensemble) is likely to impose topological restrictions, underlining the significance of the differential positioning of GATA-3 in Th1 and Th2 interphase nuclei [26].…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…2c illustrates measurements for individual GATA-3 alleles normalized to the nuclear radius, confirming the preferential association of GATA-3 with centromeric heterochromatin in polarized Th1 but not Th2 cells (p<0.01). This preferential association persisted in long term T cell lines and clones (p<0.01, Th1 clone D5 [23] versus Th2 clone D10 [24] and Th2 line GAD [25]). The cytogenetic position of the GATA-3 locus only 9.8 Mb from the centromere of chromosome 2 (Ensemble) is likely to impose topological restrictions, underlining the significance of the differential positioning of GATA-3 in Th1 and Th2 interphase nuclei [26].…”
Section: Resultsmentioning
confidence: 87%
“…Th1 cells were moved from antibody-coated to fresh culture wells 2 h after restimulation to minimize activation-induced cell death (not shown). T cell clones D5 (Ar-5) [23] and D10 (D10.G4.1) [24] were cultured in Dulbecco's modified Eagle's medium supplemented with 10% FCS, L-glutamine, penicillin-streptomycin, nonessential amino acids, sodium pyruvate, vitamins, HEPES, and 2-ME and 20 U/ml human rIL-2 (for D5) or 25 U/ml recombinant IL-4 (for D10). PGL2 (Th1) and PL104 (Th2) clones and the Th2 anti-GAD 524-543 T cell line have been described [25,42].…”
Section: Mice and Cellsmentioning
confidence: 99%
“…In these studies, it was found that a change of one or two residues in the amino acid sequence of either A or MHC caused a loss of recognition (Keck, 1975;Zinkernagel, 1976;Maizels et al, 1980;Whitmore and Gooding, 1981;DeWaal et al, 1983;Townsend et al, 1983a, b;Berkower et al, 1984;Lin et al, 1984). Other studies have indicated that hapten-specific T-cells' are also capable of recognizing subtle differences in hapten structures (Gell and Silverstein, 1962;Silverstein ?nd Gell, 1962;Janeway et al, 1975Janeway et al, , 1976aLevy and Shearer, 1982;Rao et al, 1984).…”
Section: Paradoxical Aspects Of T·cell a Specificitymentioning
confidence: 99%
“…The Ar-5 T-cell clone (37) was used for preparation of nuclear extracts and Northern (RNA) analysis of cytoplasmic RNA. All cells were maintained in Dulbecco's modified Eagle's medium containing 10% fetal calf serum, 50 ,uM 2-mercaptoethanol, 2 mM L-glutamine, 10 mM N-2-hydroxyethylpiperazine-N'-2-ethanesulfonic acid (HEPES), penicillin, streptomycin, and additives as previously described (37,47) (34). Standard curves using recombinant lymphokines were included for each experiment.…”
mentioning
confidence: 99%